Economic reforms, poverty, income distribution and employment - Dev, S. Mahendra (2000)
The paper puts together various indicators on poverty, income distribution and employment in the pre- and post-reform periods, identifying the components of reforms having impact on these indicators. Given the newly emerging disparities with regard to urban and rural, poverty, interstate inequalities, and agricultural sector, the paper argues for a more emphasis on agricultural growth and rural infrastructure, increasing social sector expenditure, and involvement of local level institutions during the phase of second generation of reforms. - Reproduced
Keywords: Employment - India; Income distribution - India; Poverty - India; Economic reform - India; Economic reform